Additions to and revisions of the vascular plant flora of the Kostomukshsky Strict Nature Reserve (Republic of Karelia) - Кравченко, Алексей Васильевич; Майорова, Людмила Викторовна; Сиккиля, Наталья Сергеевна; Хейккиля, Раймо; Kravchenko, Alexey; Mayorova, Ludmila; Sikkilä, Natalia; Heikkilä, Raimo (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2017)
Information on the distribution of 61 vascular plant species new to the Kostomukshsky Strict Nature Reserve as addition to the previous check-lists is provided. The relevant information gleaned from herbarium labels, and brief comments on the distribution in the region are given for each taxon. Thalictrum х andrzejowskii is reported from Karelia for the first time. For Galium physocarpum the locality discovered in the Reserve is the 4th, for Bromus commutatus - 5th, and for Carex praecox - 11th in Karelia. The findings of Arabidopsis suecica, Euphorbia cyparissias, Galium physocarpum, Galium х pomeranicum, Hypopitys monotropa, Ranunculus cassubicus aggr., Thalictrum simplex, Viola х contempt and Viola х wittrockiana in the Reserve are the northernmost in Karelia, or the most remote from other previously known locations. Botrychium lanceolatum and Hypopitys monotropa are listed in the Red Data Book of the Republic of Karelia (2007).